A 10-bit 300 MS/s 5.8 mW SAR ADC with two-stage interpolation for PET imaging - Qiu, Lei (2020)
In this paper, a high speed low power 2b/cycle successive approximation register (SAR) analog-To-digital converter (ADC) is proposed for medical imaging. The ADC adopts a two-stage differential pair based interpolation technique that can reduce resolution of the capacitive DAC and avoid usage of smaller unit capacitor. A meta-stability immunity technique is proposed to enhance the asynchronous conversion. A design example of 10-bit 2b/cycle SAR ADC with sampling rate up to 300 MS/s is fabricated. Dissipating 5.8 mW with 1.2 V supply and occupying an active area of 0.082 mm2, the measured SFDR and SNDR at Nyquist input are 59-dB and 51.5-dB respectively. It achieves an effective resolution bandwidth of 360 MHz and a figure-of-merit of 61fJ/conversion-step.